GENETIC POLYMORPHISM OF RETROPERITONEAL MYXOID LIPOSARCOMA - A. Yu. Volkov; V. M. Safronova; S. N. Nered; L. N. Lyubchenko; I. S. Stilidi (Сибирский онкологический журнал, 2020)
Objective: to detect new molecular genetic markers and therapeutic targets in retroperitoneal myxoid liposarcoma.Material and Methods. DNA samples isolated from tumor tissue and obtained from formalinfixed paraffin-embedded (FFPE) slides were used. DNA was extracted using the GeneRead DNA FFPE Kit (50) (Qiagen). High-throughput next generation sequencing (NGS) using the GeneReader Actionable Insights Tumor Panel (GRTP – 101X) on the QCI Analyzer version 1.1 platform (Qiagen) was used for molecular genetic analysis of 12 genes involved in carcinogenesis: KRAS, NRAS, KIT, BRAF, PDGFRA, ALK, EGFR, ERBB2, PIK3CA, ERBB3, ESR1, RAF1.Results. Targeted sequencing of retroperitoneal extra-organ myxoid liposarcoma demonstrated genetic heterogeneity. Our study was the first to describe mutations and polymorphic variants in genes, such as EGFR, PIK3CA, ALK, BRAF, ERBB2 / 3, ESR1, KIT, PDGFRA in myxoid liposarcoma.Conclusion. This study demonstrated a wide range of molecular genetic rearrangements in retroperitoneal extra-organ myxoid liposarcoma. Synonymous mutations in the EGFR (Q787Q) and PDGFRA (P567P) genes were detected in all cases (100 %). Missense mutations in the ERBB2 gene (P1170A) and synonymous mutations in the ALK (G845G) and BRAF genes were identified in 75 % of cases. Missense mutation in the PIK3CA gene (I391M) was detected in 25 % of cases. The gene polymorphisms presented in this paper are most likely involved in the carcinogenesis of retroperitoneal myxoid liposarcoma. Further studies with larger patient groups and multivariate analysis of long-term treatment results are required.